2017
DOI: 10.1590/0100-69912017001005
|View full text |Cite
|
Sign up to set email alerts
|

Profile of thoracic trauma victims submitted to chest drainage

Abstract: Objective: to describe and compare the variables involved in trauma victims undergoing thoracic drainage. Methods: we conducted a retrospective, analytical, descriptive, cross-sectional study, with medical records of patients attended at the Trauma Service of the Curitiba Evangelical University Hospital between February 2011 and January 2014. Results: there were 488 patients undergoing chest drainage, 84.7% men and 15.3% women, with an average age of 38.2 years. Attendances usually occurred at night, without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
6
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 12 publications
5
6
0
3
Order By: Relevance
“…There was a dissonance in relation to other studies performed in Goiania and São Paulo, which showed a greater incidence of penetrating injuries 4,21 . The most common mechanism of blunt TT was car accidents involving motorcycles (39.6%), in concordance with medical literature 3,20,22,27 . The second more prevalent cause were falls, a mechanism that predominates among the elderly, with 66.6% of the events in this age range.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…There was a dissonance in relation to other studies performed in Goiania and São Paulo, which showed a greater incidence of penetrating injuries 4,21 . The most common mechanism of blunt TT was car accidents involving motorcycles (39.6%), in concordance with medical literature 3,20,22,27 . The second more prevalent cause were falls, a mechanism that predominates among the elderly, with 66.6% of the events in this age range.…”
Section: Discussionsupporting
confidence: 86%
“…As well as in our research, other studies [21][22][23] showed rib fractures as the most preponderant lesions in closed TT. With regard to injuries caused by open trauma, hemopneumothorax was the most frequent finding (46.1%), as found by Souza et al 4 and Broska Junior et al 20 , but divergent from Scapolan et al 21…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Penetrating heart injuries represent a significant mortality cause, and can be challenging either from the therapeutic or the diagnostic point of view, since they can be asymptomatic or oligosymptomatic for a variable period after a trauma occurs 6,11,14 . Most studies show that young men are the most struck by penetrating heart injuries, which is in consonance with our outcomes 5,7,8,[14][15][16][17][18] .…”
Section: Discussionsupporting
confidence: 88%